ASUHAN KEPERAWATAN PADA BY. Ny.D DENGAN BBLR DI RUANG PERINATAL RSUD KRT SETJONEGORO WONOSOBO - Khaufiyah, Malia Dawi; Setyawati, Ari; Nugraheni, Ikhda (Jurnal Ilmiah Kesehatan, 2022)
LBW is a baby born with a weight <2500 grams without gestation period. Problems that are often encountered due to low birth weight are at risk of problems in the body system, due to unstable body conditions. LBW is one of the main factors in increasing neonatal mortality, morbidity and disability. LBW has a 35 times higher chance of dying than babies born with a birth weight above 2500 grams. The purpose of this research is to provide nursing care for children withIneffective breathing pattern related to respiratory muscle weakness.